DEIXIS FOUND IN KAMIO YOUKO’S HANA YORI DANGO IN ENGLISH VERSION - Mariska Febrianti (JOALL (Journal of Applied Linguistics and Literature), 2017)
Deixis cannot be separated to language itself because deixis is a part of language. One of language forms in our environment are comics. It is the popular literary works that teenager read besides novel and short story. The objectives of this research can be further detailed as the following; (1) To find kinds of deixis that are in Kamio Yuoko’s Hana Yori Dango. (2) To know the situation of deixis are in  Kamio Youko’s Hana Yori Dango. The design of this research is descriptive qualitative research. It describes deixis found in Hana Yori Dango comic. This research uses the descriptive qualitative research. The result of this research are; (1) The kinds of English deixis found in Hana Yori Dango comic are; eighty five person deixis, twelve place deixis, thirteen time deixis, thirteen social deixis, and seventeen discourse deixis. So, it can be concluded the the dominan deixis which is used in Hana Yori Dango comic is person deixis and the minor deixis is place deixis and (2) The dominant situation in Hana Yori Dango comic is utterance situation related to person and social deixis in finding. So, the theory of deixis analysis from Jaszczolt (2002, p.191) is sticked with the result of deixis found in Hana Yori Dango comic. In this study, the kinds of deixis most commonly found is person deixis. It indicates that the author extremely want to show the figures in the story of comic. It can be seen from the portion of conversation made by the author is simple and short utterance and also related to some elements in comic itself.